Exploring Destination Choice Intention by Using the Tourism Photographic: From the Perspectives of Visual Esthetic Processing - Deng, Weiwei; Lin, Yingxing; Chen, Lijun (Frontiers in Psychology, 2021)
This study aims to deepen understanding the tourism photographic by developing and testing theoretical model that account for the relationships between tourists’ visual esthetics and destination choice intention. Thus, we sought to use a Stimulus-Organism-Response paradigm to predict destination choice intention, which includes three variables related to visual esthetics: first impression, visual appeal, and esthetic emotion. We use the combination of self-reported and eye movement data to examine the tourists’ cognitive processes that visual esthetic formation. We found that compared to the built environment and amateur esthetics images, natural environment and professional esthetics images can to get: 1) higher visual appeal; 2) better first impression; 3) higher visual processing fluency (or less cognitive effort) and positive esthetic emotions. Furthermore, visual appeal, first impression, and esthetic emotion deriving from environment esthetics and photograph esthetics have a positive impact on destination choice intention. This study has practical implications for destination planning and management.